2019
DOI: 10.1038/s41598-019-49848-w
|View full text |Cite
|
Sign up to set email alerts
|

Activation volume in superpressed glass-formers

Abstract: In pressurized glass-forming systems, the apparent (changeable) activation volume Va(P) is the key property governing the previtreous behavior of the structural relaxation time (τ) or viscosity (η), following the Super-Barus behavior: , T = const. It is usually assumed that Va(P) = V#(P), where or . This report shows that Va(P) ≪ V#(P) for P → Pg, where Pg denotes the glass pressure, and the magnitude V#(P) is coupled to the pressure steepness index (the apparent fragility). V#(P) and Va(P) coincides only for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…It is emphasized that eq is only an approximation that may naturally be derived by expanding the activation free energy about the limit of zero pressure and only keeping the leading term in P , but we do not pursue this extension in the present paper. Recently, a P -dependent activation volume has been studied for the P regime beyond the linear regime in which eq holds, but we restrict our attention to the conventional definition of activation volume in the materials science literature in the present work. In previous works, , we have examined the influence of high pressures on the dynamics of GF polymer melts based on a different framework to account for the high pressure dependence of the activation free energy.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is emphasized that eq is only an approximation that may naturally be derived by expanding the activation free energy about the limit of zero pressure and only keeping the leading term in P , but we do not pursue this extension in the present paper. Recently, a P -dependent activation volume has been studied for the P regime beyond the linear regime in which eq holds, but we restrict our attention to the conventional definition of activation volume in the materials science literature in the present work. In previous works, , we have examined the influence of high pressures on the dynamics of GF polymer melts based on a different framework to account for the high pressure dependence of the activation free energy.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We again emphasize that the definition of Δ V # in eq involves a physical approximation in the sense that lnτ α does not vary linearly with P at high P . Beyond the linear pressure regime in which eq holds, a P -dependent activation volume might be formally defined, but this is not the focus of the present work. While both the GET and MD simulations have indicated that ln τ α can grow with P in a fashion following a pressure analogue of the VFT equation, a linear relationship between ln τ α and P is expected to hold when P is sufficiently low.…”
Section: Results and Discussionmentioning
confidence: 99%
“…While there has been long-term interest in Δ V # in the engineering community because of the relevance of this quantity to controlling changes in relaxation processes, diffusion, and rates of reactions under various types of applied stresses, , where varying pressure is perhaps the most common type of applied stress, a growing appreciation has emerged for connecting Δ V # with an understanding of the fundamental aspects of glass formation. There has been particular interest in separating out aspects of glass formation relating to the effects of attractive intermolecular interactions, temperature, and density. ,, These efforts have naturally led to systematic studies of glass formation over a wide range of pressures to complement the traditional studies at fixed pressure and variable temperature. , In addition to the development of new expressions for the dependence of τ α on pressure, this type of study has naturally led to a definition of glass “fragility” relating to the differential rate of change of log τ α with respect to pressure at a characteristic P at which glass formation occurs at fixed T , in analogy with the “steepness index” measure of fragility from the apparent activation energy determined in an Arrhenius plot for τ α near T g .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In several other liquids, PG (31)(32)(33), glycerol (8,34), and OTP (8), the temperature of P 0 percolation appears to have been mistaken for T A and T B by some authors.…”
Section: Resultsmentioning
confidence: 99%